Glycerol accumulation and modulation in selected enzyme activities in response to cold acclimation of two species of cyprinid fishes Schizothorax richardsonii (Gray) and Barilius bendelisis (Hamilton) - Tyagi, Ankita; Ali, Shahnawaz; Goel, Chirag; Barat, Ashoktaru (Indian Journal of Fisheries, 2014)
Glycerol accumulation in blood plasma and modulation in the activities of selected enzymes associated with glycerol synthesis in the liver under cold temperature were assessed in two freshwater cyprinid fishes, Schizothorax richardsonii (snow trout) and Barilius bendelisis (Indian hill trout). Fishes were collected from Kosi River, Uttarakhand during late October 2011 (water temperature 15-16 0C) and after an acclimatisation for 7 days they were maintained at lower temperature of 5 0C over a period of 96 h. The decrease in temperature triggered higher accumulation of glycerol in the blood plasma of both the species. Glycerol accumulation in plasma was found to be associated with changes in enzyme in the liver. In both the species, liver exhibited higher activities of glycerol-3-phosphate dehydrogenase (GPDH) and higher concentration of dihydroxy acetone phosphate (DHAP) which gets converted into glycerol. The increased activities of different enzymes involved in amino acid metabolism indicated the utilisation of amino acids as carbon source in glycerol synthesis. The measure of enzymes associated with gluconeogenesis indicated typical gluconeogenic pathway associated with glycerol synthesis. Based on the enzyme profile studied, it was established that the freshwater cyprinids; S. richardsonii and B. bendelisis, a decrease in water temperature triggered the release of glycerol in the blood plasma and also activated metabolic response for glycerol accumulation. The higher accumulation of glycerol seems to contribute towards cold adaptation in these species.